PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, PROFITABILIAS, SOLVABILITAS, DEBT TO ASSET RATIO, EARNING PER SHARE, DAN UKURAN PERUSAHAAN AUDIT TERHADAP AUDIT DELAY - Gita Melosa; Abdul Rohman (Diponegoro Journal of Accounting, 2022)
This study was made with the aim of knowing the effect of company size, liquidity, profitability, solvability, debt to asset ratio, earning per share, and audit firm size, on audit delay in consumer goods companies listed on the Indonesia Stock Exchange (IDX) in the period of observation from 2018 to 2020. Independent variables on this research are company size, liquidity, profitability, solvability, debt to asset ratio, earning per share, and audit firm size. The dependent variable in this study is audit delay.            This study has a population that is consumer goods companies listed on the Indonesia Stock Exchange (IDX). Purposive sampling method is used to take samples that will be used in this study, with a total sample of 123 company samples. Sources of data used in this study are secondary data from audited financial reports and company annual reports published through the Indonesia Stock Exchange (IDX) website as well as through the respective companies’ websites. Multiple linear regression technique and independent sample t-test are the analytical method used in this study.            The results of the study found that profitability and earning per share have negative effect on audit delay. Meanwhile, debt to asset ratio has a positive effect on audit delay. Firm size, liquidity, solvability, and audit firm size do not affect audit delay. Thus, from the seven independent variables, partial test results show that only three variables that affect the audit delay.